Cutaneous T-cell lymphomas (including rare subtypes). Current concepts. II - M Paulli; E Berti (Haematologica, 2004)
BACKGROUND: Cutaneous T-cell lymphomas (CTCL) represent about the 80% of skin lymphomas and comprise a heterogeneous group of diseases with respect to clinical presentation, outcome, histologic and immunophenotypic features. In the recent years, data have been accumulated indicating that clinical and biological differences exists between primary nodal and primary extranodal lymphomas. INFORMATION SOURCES: On such bases, the cutaneous lymphoma classification by the EORTC (European Organization for Cancer Research and Treatment) but also the recent general lymphoma classification, by the WHO (World Health Organization), have dedicated special attentions to the cutaneous lymphomas including the T and NK-cell subtypes. This paper reviews the most significative subtypes of T-cell lymphoma that affect the skin primarily or secondarily. STATE OF THE ART: Apart from mycosis fungoides with its variants forms and the Sezary’s syndrome, we have focused on the CD30+ primary cutaneous lymphoproliferative disorders (PCLD) (25% of all CTCL), a fascinating spectrum of disease, extending from lymphomatoid papulosis (LyP) trough to CD30+ large cell lymphoma. These disorders have in common large atypical CD30+ cells and a frequent spontaneous regression of the skin lesions associated with a relatively favourable outcome (excellent in LyP). The identification of this group of skin disorders is crucial for the patients since most of CD30+ PCLD are indolent diseases that do not warrant aggressive treatment. Others types of CTCL include the heterogeneous category of peripheral T-cell lymphoma not otherwise specified (NOS), subcutaneous panniculitis-like T-cell lymphoma and the still controversial group of the cytotoxic lymphomas. PERSPECTIVES: Notably, the latter two subtypes have special relevance to the clinicians because (i) subcutaneous panniculitis-like T-cell lymphoma may be associated with the hemophagocytic syndrome; (ii) skin lesions in cytotoxic lymphomas may represent the first manifestation of an otherwise systemic disease.